DIVERSITY AND DISTRIBUTION OF PLASMODIAL MYXOMYCETES (SLIME MOLDS) FROM LA MESA ECOPARK, QUEZON CITY, PHILIPPINES - SITTIE AISHA B. MACABAGO; NIKKI HEHERSON A. DAGAMAC; THOMAS EDISION E. DELA CRUZ (BIOTROPIA, 2010)
Myxomycetes are ubiquitous in terrestrial forest ecosystems. Thus, this research study looks at the taxonomic diversity and distribution of plasmodial myxomycetes in La Mesa Ecopark in Quezon City, Philippines. A total of 240 moist chambers were prepared from four substrates (aerial and ground leaf litter, twigs and barks) collected within this ecopark. Following incubation of moist chambers for eight weeks, a total of 28 species belonging to 10 genera were collected and identified: Arcyria (3), Diderma (2), Didymium (5), Lamproderma (2), Perichaena (3), Physarum (8), Macbrideola (1), Metatrichia (1), Trichia (1) and Stemonitis (2). Highest myxomycete yield (85%) was observed in aerial leaf litter. In terms of taxonomic diversity, highest diversity was observed in bark microhabitats, although the lowest number of species was recorded in it. Assessment of their abundance and distribution showed similarities in species composition between aerial and ground leaf litter. This research study is the first report of plasmodial myxomycetes in La Mesa Ecopark in Quezon City, Philippines.   Keywords: myxomycetes, slime molds, microhabitats, recreational forest